Communicating discharge instructions to patients: A survey of nurse, intern, and hospitalist practices1. Issue 1 (15th October 2012) - Ashbrook, Liza; Mourad, Michelle; Sehgal, Niraj
Abstract BACKGROUND: Comprehensive discharge education can improve patient understanding and may reduce unnecessary rehospitalization. OBJECTIVES: To understand nurse and physician communication practices around patient discharge education. SETTING: University of California, San Francisco Medical Center (UCSFMC). PARTICIPANTS: Nurses, interns, and hospitalists caring for hospitalized medicine patients. MEASUREMENTS: Participants were surveyed regarding discharge education practices. The survey asked respondents about 13 elements of discharge education found in the literature. For each element, participants were queried regarding: 1) the provider responsible for this element of patient education; 2) the frequency with which they communicate this teaching to patients; 3) how often they directly communicate with the nurse or physician caring for the patient about each element; and 4) tools to improve nurse–physician communication. RESULTS: A total of 129/184 (70%) nurses, interns, and hospitalists responded to the survey. The majority of respondents in all 3 groups felt that 9 of 13 elements were a combined responsibility. Nurses reported educating patients on these 9 items significantly more often than physicians (P < 0.05). All groups also agreed that instruction on 2 of the elements, summary of hospital findings and pending results, should be primarily the physicians' responsibility; these were the elements least often discussed by any provider. Despite the majority of items being agreed upon as a shared responsibility, communication between nurses and physicians regarding discharge education was low. Standardized verbal communication on the day of discharge was supported most strongly by all providers. CONCLUSIONS: Ambiguous responsibility for providing discharge education and poor communication between nurses and physicians offers an opportunity for improvement. Journal of Hospital Medicine 2013. © 2012 Society of Hospital Medicine